Actively dying : the creation of Muslim identities through end-of-life care in the United States - Hughes Rinker, Cortney (Abingdon, Oxon ; New York : Routledge, 2021)
"This book explores the experiences of Muslims in the United States as they interact with the health care system during serious illness and end-of-life care. It shifts "actively dying" from a medical phrase used to describe patients who are expected to pass away soon or who exhibit signs of impending death, to a theoretical framework to analyze how end-of-life care, particularly within a hospital, shapes the ways that patients, families, and providers understand Islam and think of themselves as Muslims. Using the dying body as the main object of analysis, the volume shows that religious identities of Muslim patients, loved ones, and caregivers are not only created when living, but also through the physical process of dying and through death. Based on ethnographic and qualitative research carried out mainly in the Washington, D.C. region, this volume will be of interest to scholars in anthropology, sociology, public health, gerontology, and religious studies"--
Death and dying within the US health care system -- Islam and end-of-life care : prevalent approaches and beliefs -- Muslim health care providers : the intersection of medical practice and religion -- The Muslim child : adult children caring for dying parents -- Death : the dead Muslim body and connections to identity -- The important case of "a bus" : a critique and intervention.
OCLC-licensed vendor bibliographic record.
Keywords: Muslims -- Medical care -- United States; Medical care -- Religious aspects -- Islam; Terminal care -- United States; Muslims -- Social life and customs; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Death & Dying